A Sikh wedding - Bennett, Olivia; Taylor, Liba (London : H. Hamilton, 1985)
Photographs and text describe the events at a Sikh wedding, including the preparations, customs, ceremonies, and celebrations
Keywords: Marriage customs and rites, Sikh -- India; Sikhs -- Social life and customs